Parent-child sexual and reproductive health communication among very young adolescents in Korogocho informal settlement in Nairobi, Kenya - Beatrice W Maina; Boniface Ayanbekongshie Ushie; Caroline W Kabiru (BMC, 2020)
Abstract Background Parents are an important source of sexual and reproductive health (SRH) information for very young adolescents and are likely to have a significant influence on adolescents' sexual attitudes, values, and risk-related beliefs. This study explored the nature and content of parent-child communication about SRH issues. Methods Thirty-two parents and 30 adolescent boys and girls aged between 11 and 13 years participated in narrative interviews in a resource-poor urban setting in Nairobi, Kenya. Interviews were audio-recorded, transcribed, translated into English, and uploaded on Atlas.ti software for coding and analysis. Results Findings from the study show gender differences in parent-child communication. More girls than boys reported that they had talked with their parents about romantic relationships. Four approaches-no communication, fear-based communication, supportive communication, and involving an external person were used by parents in SRH communication. Parents hostile attitudes towards romantic relationships during adolescence discouraged adolescents from disclosing their relationship status. While communication did occur, it was mainly reactive, one-sided, and authoritarian, often initiated by parents. Conclusions Parents need to be empowered with adequate and factual SRH information and effective communication strategies to enhance communication with very young adolescents. There is a need for further research to identify the most effective parent-child communication approaches to improve SRH outcomes among adolescents.